Effect of lime, potassium, sulfur and micronutrients on the growth of Centrosema pubescens in acid soil - Oliveira, Fábio Teotônio Teixeira de; Saraiva, Odilon Ferreira; Carvalho, Margarida Mesquita de; Verneque, Rui da Silva (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was undertaken in a glasshouse to study the effect of lime, K, S, Zn, Cu, B and Mo, at two levels, on the growth nodulation and nitrogen fixation of Centrosema pubescens Benth in a Red-Yellow Latosol. Rates of lime and nutrients in kg.ha-1 were: lime, o and 4,000; K, 0 and 100; S, 0 and 30; Zn, 0 and 4.5; Cu, 0 and 2.5; B, 0 and 1.0; Mo, 0 and 0.38. Liming had a large effect in increasing dry weight of tops and roots, nodule number and dry weight and N concentration in the tops. There was a significant lime x K interaction, so that in the absence of lime, K depressed root dry weight, but in the presence of lime, K increased nodule number and dry weight. Molybdenum increased symbiotic N2 fixation. Results suggest that centrosema would respond to Zn, especially in the presence of lime. The application of S, Cu and B had no effect on the centrosema growth or symbiotic N2 fixation.